Midiagramas: uma abordagem diagramática dos objetos da comunicação - Ribeiro, Maria Angélica Souza (2014)
We propose a theoretical and diagrammatic approach of objects of communication. Then, a theoretical-diagrammatic approach suggests that media objects are investigated from their structural correspondence with the set of theoretical propositions devised by the researcher. Likewise, when we refer to diagrams (like a sign of iconic dominance) and objects of communication, we insist on the epistemological nature of the research. Beforehand, we should indicate what is specific in the communication object or underline their distinctive features when compared to other objects (from psychology, theology, and economics, for example). Then, we need to determine the basis for a semiotics of communication as a disciplinary field. This research aims to contribute to the repertoires of epistemological and methodological studies in Communication. Our main hypothesis considers the diagrammatic reason as a theoretical resource combined with the cognitive consequences of new technologies. This, in some sense, have inspired a kind of research located at the convergence of media artifacts and scientific rationality